Recombinant 60-kDa heat shock protein from Paracoccidioides brasiliensis: is it a good antigen for serological diagnosis of paracoccidioidomycosis? - Peron, G. (Braz J Med Biol Res, 2017)
Paracoccidioides brasiliensis and P. lutzii are fungi that cause paracoccidioidomycosis (PCM), the most prevalent systemic mycosis in South America. For serological diagnosis, although 43-kDa glycoprotein (gp43) is regarded as highly specific for PCM, the occurrence of false negative reactions in sera from patients infected with P. lutzii suggests that preparation with only one antigen is not recommended. Heat shock proteins are feasible alternatives as a second antigen because they are often highly immunogenic. In this study, we evaluated the usefulness of recombinant 60-kDa heat shock protein from P. brasiliensis (rPbHsp60) for the serological diagnosis of PCM. Using western blotting assay, we observed that 77.3% of the sera from PCM patients were positive to rPbHsp60, with 90.9% positivity to recombinant gp43 (rgp43). More importantly, sera from healthy subjects had 27% positivity to rPbHsp60 and none to rgp43. When rPbHsp60 was used in ELISA, we did not observe significant differences between the reactions with sera from PCM patients and healthy subjects, while the difference was clearly evident when the antigen was rgp43. Furthermore, rPbHsp60 was recognized by sera from patients with histoplasmosis, aspergillosis, sporotrichosis or tuberculosis in an ELISA test. These results show that rPbHsp60 is not a good antigen for PCM diagnosis.